Regulatory support of disciplinary proceedings in Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The article features the study and analysis of the sources for regulatory support of disciplinary proceedings in Ukraine, depending on the type of disciplinary responsibility.As a result of the study of the content of the regulatory support of disciplinary responsibility, the formulation of the following terms as “Disciplinary Proceedings”, “Labor Discipline”, “Service Discipline”, “Disciplinary Offense”, “Simple and Gross Disciplinary Offense”, which differ according to a regulatory act, have been analyzed.The article defines that disciplinary proceedings in Ukraine are regulated by a wide range of regulatory acts, which shall reasonably be combined, both according to the types of disciplinary responsibility, and on subjects of disciplinary responsibility. According to the types of disciplinary responsibility, the sources of regulatory support are divided into those that regulate a general disciplinary responsibility, special disciplinary responsibility, disciplinary responsibility in accordance with the norms of correctional law and disciplinary responsibility of students. The sources for regulatory support, that regulate a special disciplinary responsibility, in their turn, can be divided into types of subjects of disciplinary responsibility (prosecutors, judges, civil officers, employees of the National Police, etc.), which determines the specific nature of disciplinary proceedings.As a result of the study on the regulatory support of disciplinary proceedings in Ukraine, the directions have been identified that require further improvement and development. They are: the need of unification of conceptual and categorical framework, in particular of the concepts of “Disciplinary Proceedings”, “Labor Discipline”, “Service Discipline”, “Disciplinary Offense”; eliminating legal gaps on explanation and specification of the list of grounds for bringing to disciplinary responsibility; as well as ensuring objectivity concept in disciplinary proceedings by clearly specifying the division of disciplinary offenses into simple and gross in the regulatory support sources.